EFFECT OF COFFEE FARMERS CAPACITY ON PERFORMANCE OF COFFEE INDUSTRY IN KENYA - Kuguru, Peter Ngibuini (European Journal of Business and Strategic Management, 2016)
Purpose: This study sought to determine the factors affecting the performance of the coffee industry in Kenya with a case study of Mathira Constituency. The study sought to find the existing linear relationship between the factors affecting the coffee industry and performance of the coffee industry. The factors that were considered included growers skills, growers level of education and level of technology awareness. The study was grounded on public interest theory of regulation, total quality management theory and Theory of Performance. Methodology: Mixed mode research approach was used which consisted of the descriptive research design and correlation research design. Simple random sampling technique was used and the sample consisted of 385 respondents out of a population of 26,000 farmers. The study involved a primary data collection from the coffee farmers and the coffee cooperative society managers. The collected data was edited, coded, keyed in and analyzed using Statistical Package for Social Sciences (SPSS). Results: Results showed that grower's capacity have significant effects on coffee industry performance in Kenya. The results show that majority of the respondents represented by 83.60% agreed and strongly agreed that limited grower's capacity in coffee industry has led to low performance of coffee industry in Kenya. In addition the results indicated that grower's capacity has a positive and significant relationship with coffee industry performance. Further the results indicated that an increase of 0.431 will result in a corresponding one unit increase in performance of coffee industry in Kenya. Unique contribution to theory, practice and policy: This study recommended that farm inputs loans should be re-introduces, taxes on farm input harmonized, and the government should ensure that CBK is corruption free to pump new energy into the Kenya coffee industry.